PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA DI DEALERPT. NUSANTARA SAKTI CABANG MANDONGA KOTA KENDARI - Sulaiman; Ibnu Hajar; La Ode Almana (STIE ENAM ENAM KENDARI, 2022)
The purpose of the study was to determine the effect of the marketing mix on purchasing decisions for Honda motorcycles at Dealer PT. Nusantara Sakti Mandonga Branch, Kendari City. The population in this study were all consumers of PT. Nusantara Sakti Mandonga Branch, Kendari City, who bought 278 Honda motorcycles in 2021. The sample of this study was 74 respondents using the slovin method. The type of data used in this study is primary data. The data analysis method used is quantitative descriptive analysis. The analytical tool used is simple Linear Regression. The results of the study stated that the marketing mix which includes; product, price, place and promotion have a positive and significant effect on purchasing decisions, meaning that the higher or better the marketing mix, the purchasing decisions will increase.